Produções orais de um primeiro ano de ensino médio noturno à luz da situacionalidade e da argumentação - Albiero, Monize Pereira (2020)
In this master's dissertation, linked to Postgraduate Program in Letters (PPGL) of the Federal University of Santa Maria (UFSM), we present a research developed in a classroom, at the state basic school Cícero Barreto, located in Santa Maria, in the state of Rio Grande do Sul. The general objective is verifying if, from the action research and from the principle of the situationality of textual construction of the sense, it is possible to qualify the argumentation of the nightly high school students with the support of the ruled public debate genre. The specific objectives are: investigating the relationship between the principle of situationality and the argumentative construction; and verifying the nature of the types of arguments in the constitution of the defense from a point of view. For this purpose, our theoretical framework is anchored, mainly, in the studies of: Beaugrande and Dressler (1981), Koch (1985; 2014; 2015; 2018), Marcuschi (2008; 2010; 2011; 2012), Bakhtin (1997; 2009), Kerbrat-Orecchioni (2006) besides Perelman and Olbrechts-Tyteca (2014). In the methodological framework, we base ourselves on the action research which was explored by scholars such as: Carr e Kemmis (1988), Burns (1999) and Thiollent (2011). This methodology allows the realization of a participative investigating, in order to involve, in this work, researcher-teacher and students-participants of the research in the process of datas’ generation. This process occurred through the organization of five workshops, from July to December of 2018, which were held in eighteen face-to-face meetings during the Portuguese language classes with a first-year class of nightly high school. According to Dolz, Noverraz and Schneuwly (2004), we used the didactic sequence as methodological tool. Our corpus is composed by transcriptions of three debates held with that class and our categories of analysis are: the situationality, through its twelve strategies, and the argumentation, from the types of arguments. In a qualitative analysis, with emphasis on the oral production of S22 – our research subject - we contextualize and comment each debate analytically. From the theoretical framework of the Text Linguistics and of the interactional socio-cognitive perspective, defended in official documents such as Parâmetros Curriculares Nacionais (BRASIL, 2000) and the Base Nacional Comum Curricular (BRASIL, 2018), we elaborate materials and, in classroom, we develop a work whose central object is the argumentative text. As a result, we highlight that, from our analysis categories, we evidence a gradual advance in the argumentative qualification of our subject of analysis. In Debate 1, the initial production of our didactic sequence, S22 used the strategies 2:b, 4 and 6 and the arguments of person and precedent; in Debate 2, which was a support activity of one of the modules, S22 used the strategies 2:b and d, 4 and 6 and the arguments of rule of justice, retorsion, example, direction, precedent and pragmatic; in Debate 3, the final production, S22 used the strategies 2,b, c and d, 3,4,5,6,7,9 and 11 and the arguments of autophagy, precedent, expressive definition, direction, comparison, authority, pragmatic and appearance/reality.